2005
DOI: 10.1080/13670050508668623
|View full text |Cite
|
Sign up to set email alerts
|

From Literacy in Māori to Biliteracy in Māori and English: A Community and School Transition Programme

Abstract: Teachers and community in a small rural Māori-medium school in New Zealand were concerned that their students who were highly literate in Māori experienced difficulties in reading and writing in English on entry to secondary school (where English was the medium of instruction). Consequently, this school and community introduced a 10-week culturally appropriate home and school English reading and writing programme for their Year 6, 7 and 8 students. Specific tutoring procedures were implemented to assist studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Te reo Māori is a transparent orthographic language (the alphabetic symbols are consistent with their sounds), whereas English is orthographically opaque (letters have more than one sound association) and has irregular spelling rules (Caravolas et al, 2005;Glynn et al, 2005). Te reo Māori also has a less complex syllable structure and minimal consonant clusters compared to the English language.…”
Section: Biliteracy Learningmentioning
confidence: 99%
“…Te reo Māori is a transparent orthographic language (the alphabetic symbols are consistent with their sounds), whereas English is orthographically opaque (letters have more than one sound association) and has irregular spelling rules (Caravolas et al, 2005;Glynn et al, 2005). Te reo Māori also has a less complex syllable structure and minimal consonant clusters compared to the English language.…”
Section: Biliteracy Learningmentioning
confidence: 99%
“…It was found that teachers of middle-school students can assist students' mathematical competency through incorporating an enjoyment disposition into their programmes by taking a keen interest in the culture of the students. For example, (Glynn, Berryman, Loader, & Cavanagh, 2005) found that Māori students have a need to feel respected and proud of who they are as Māori; a key process in this is teachers learning about tikanga 11 Māori from the students. Another New Zealand study (Macfarlane et al, 2007) revealed a definition of 'safety' from a Māori cultural viewpoint, where safety is perceived to mean students having the freedom to be who they are, as Māori (individually and collectively).…”
Section: Ako Promotes Student Engagement and Positivity In Their Learningmentioning
confidence: 99%